Enhancing ZIS Literacy for Optimizing Muzaki Decision to Pay ZIS Study of Social Media Effect using AISAS Model Approach - Lathifah, Fitriyani; Hilmatunnisa, Alma (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
According to changes customer behavior including zakat giver (muzaki), social media management plays an important role in increasing the literacy and action of prospective muzaki regarding to ZIS engagement wherever. Start from social media, the opportunity to optimizing ZIS collection is greater and more flexible. This research aims to analyze the optimizing muzaki decision to pay zakat using the AISAS model approach. The AISAS model provides an illustration that social media be able to increase muzaki literacy and muzaki decision to pay zakat and share their experiences of ZIS action to the other community. The results show that social media has an influence on increasing ZIS literacy through AIS (attention, interest, search) as mediating variables. Furthermore, zakat literacy has an influence on increasing desire to pay zakat, action, and sharing experience using social media. However, the influence of social media is still not optimal. The action and share (AS) variables in the AISAS model are considered to have an important role in influencing society to pay zakat.